Kemampuan Spasial Siswa SMP Laki-Laki Maskulin dan Perempuan Feminin dalam Memecahkan Masalah Geometri - Siti Suparmi; I Ketut Budayasa; Rini Setianingsih (JRPM (Jurnal Review Pembelajaran Matematika), 2022)
This study aims to describe the spatial ability of masculine male and feminine female students in solving geometric problems. The subjects of this study are one masculine male gender and one feminine female gender junior high school students who had the same mathematical ability. The subject selection was carried out using the Bem Sex Role Inventory instrument and Middle Semester Assessment scores, followed by conducting TPM (Problem Solving Test) and TPM-based interviews. The data collected from the TPM results and TPM-based interviews were then analyzed by applying the following steps: categorization, reduction, data presentation, interpretation, and conclusion. The results showed that subject-1 satisfied five indicators of spatial ability, namely spatial perception, visualization, spatial rotation, spatial relations, and spatial orientation so that it can be said to have high spatial abilities. On the other hand, subject-2 only meets three indicators of spatial ability, namely spatial rotation, spatial relation, and spatial orientation, so it can be said that female students have moderate spatial abilities. It is expected that the results of this study will be useful for future research and the mathematics learning process in schools